Community Services at SMP Bina Siswa Kotabaru Sub-district West Bekasi District in 2023 - Sasabone, Restichia; Siauta, Jenny Anna; Adinda, Paula Natasa Sindy; Sagala, Kristina; Venancyana, Maria Chandra; Purba, Rohani; Bonita, Bonita; Anggraeni, Devita (Rajaki of Tulip Medika Publisher, 2023)
Background: Health problems receive serious attention from various elements ofsociety. One way to solve health problems in the community is to carry out communityservice. Community service is an activity that aims to assist the community in severalactivities to overcome the problems they face by actively participating in the healthdevelopment process and increasing community empowerment without expecting anyform of reward. Objective: Carry out community service activities by carrying out activities rangingfrom collecting secondary data to conducting interventions and evaluating fieldactivities. Method: The practice of community midwifery carried out by Nasional UniversityMidwife Professional Education Students Batch 5 Group 3 with the practice area at theYusma Medika Clinic which was carried out at the Bina Siswa Utama Middle School,Kotabaru Subdistrict, West Bekasi District, Bekasi City, has been carried out in thefollowing stages: Orientation, Taking Secondary Data, Focus Group Discussion (FGD),Preparation of Planning Of Action (POA), Intervention activities in the form ofcounseling about